Tingkat Kepuasan Wisatawan Terhadap Kualitas Sarana dan Prasarana di Kawasan Kota Lama Semarang - Puspitasari, Meike Lintang; Sastrawan, I Gede Anom (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i02.p25, 2020)
This study aims to determine the level of tourist satisfaction with the quality of facilities and infrastructure in the Semarang Old City Area. Revitalization of the Semarang Old City Area is done by improving infrastructure and adding facilities and infrastructure. Good quality facilities and infrastructure can produce satisfaction for tourists who come. This research uses qualitative and quantitative data types, while the data sources used are primary and secondary sources. Data collection techniques used in this study were observation, questionnaires, and interviews. The measurement scale of variables uses the Likert scale. The technique of determining informants using purposive sampling. The data analysis technique used is quantitative descriptive. The results of this study are tourists most satisfied with pedestrian road and tourist most dissatisfied with bench and parking area. The condition of good facilities and infrastructure will produce satisfaction for tourists. The results of the analysis can be used as an evaluation for the manager of Semarang Old City Area.   Keyword : condition, quality, facilities, infrastructure, and satisfaction level.